2022
DOI: 10.3138/jvme-2020-0145
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Pre-Veterinary Opportunities and Recommendations for DVM Admissions

Abstract: During the summer of 2020, a survey-based study was conducted at North Carolina State University, a land-grant university, to evaluate the impact of COVID-19 on pre-veterinary students’ ability to gain experience hours for Doctor of Veterinary Medicine (DVM) admissions. Of the 286 respondents (47% of the respondent pool), 92% reported losing at least one animal, veterinary, research, extracurricular, or work opportunity due to COVID-19, and 59% were not able to find a replacement. Of the lost experiences, 74 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
0
0
Order By: Relevance
“…It is quite likely that this practice also contributed to the higher number of students who did not sit the animal nutrition exam in summer term 2020. A survey from the USA (Trivedi et al, 2021) found that due to inability for work experience and practical opportunities, some students were reluctant to apply for veterinary college. Our observation that more students did not sit the animal nutrition exam in 2020 may have had similar reasons, when some students might have been delayed in the general progress of their studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is quite likely that this practice also contributed to the higher number of students who did not sit the animal nutrition exam in summer term 2020. A survey from the USA (Trivedi et al, 2021) found that due to inability for work experience and practical opportunities, some students were reluctant to apply for veterinary college. Our observation that more students did not sit the animal nutrition exam in 2020 may have had similar reasons, when some students might have been delayed in the general progress of their studies.…”
Section: Discussionmentioning
confidence: 99%